1980
DOI: 10.1016/0042-6989(80)90063-2
|View full text |Cite
|
Sign up to set email alerts
|

Depth of focus, eye size and visual acuity

Abstract: We develop formulas for calculating the approximate depth of focus of any eye. They show that the magnitude of depth of focus is inversely proportional to the size of the eye and to its visual acuity. One particular implication of these quantitative relations. which is supported by previous data from rats and human infants, is that small eyes with low acuity should have large depths of focus. We show that the observed relation between defocus and contrast sensitivity in rats in predicted by our formulas. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
0
1

Year Published

1983
1983
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(108 citation statements)
references
References 45 publications
4
103
0
1
Order By: Relevance
“…Distant stimuli at lower elevations could be viewed in focus most simply by tilting the head. Green, Powers & Banks (1980) have estimated with Gaussian optical approximations that the 'depth of focus' of the pigeon eye is 0-3 D. In peripheral viewing the elliptical shape of the pupil will confer a meridional variation both to resolution and to depth of focus. Depth of focus will be least different from that in axial viewing where a grating is orthogonal to the long axis of the pupil.…”
Section: Discussionmentioning
confidence: 99%
“…Distant stimuli at lower elevations could be viewed in focus most simply by tilting the head. Green, Powers & Banks (1980) have estimated with Gaussian optical approximations that the 'depth of focus' of the pigeon eye is 0-3 D. In peripheral viewing the elliptical shape of the pupil will confer a meridional variation both to resolution and to depth of focus. Depth of focus will be least different from that in axial viewing where a grating is orthogonal to the long axis of the pupil.…”
Section: Discussionmentioning
confidence: 99%
“…After nine sessions, all animals were still responding at chance (50% or below) accuracy. In light of reports by Dean (1981) and Green, Powers, and Banks (1980), whose assessments of rats' visual acuity indicated that rats should be at least 20 cm from visual stimuli to achieve accurate visual discrimination, we reasoned that increasing the animals' distance from the video screen at the beginning of trials might improve performance. Accordingly, after Session 9, the chamber was modified by moving the food magazine and pellet dispenser so that pellets were delivered at the center of the rear chamber wall (see Figure IB).…”
mentioning
confidence: 99%
“…Although the actual magnitude of longitudinal chromatic aberration does not necessarily scale with eye size across species [55], its effects on image quality are theoretically worse in larger eyes (especially where the pupil is large relative to the focal length, i.e. a low f-number) as they have a shorter depth of focus (by virtue of their longer focal length) compared with small eyes [57].…”
Section: Discussionmentioning
confidence: 99%